2012
DOI: 10.1089/ars.2011.4345
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Is a Signaling Molecule and a Cytoprotectant

Abstract: Significance: Accumulating evidence shows that hydrogen sulfide may function as a signaling molecule in processes such as neuromodulation in the brain and smooth muscle relaxation in the vascular system. It also has a cytoprotective effect, since it can protect neurons and cardiac muscle from oxidative stress and ischemiareperfusion injury, respectively. Hydrogen sulfide can also modulate inflammation, insulin release, and angiogenesis. Recent Advances: The regulation of the activity of 3-mercaptopyruvate sulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
202
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(209 citation statements)
references
References 79 publications
(133 reference statements)
5
202
0
2
Order By: Relevance
“…Exogenous H 2 S supplementation reduces blood pressure, decreases atherosclerotic plaque size compared with those of controls in apolipoprotein E knock-out mice, and prevents progression of diabetic nephropathy in spontaneously hypertensive rats and endothelial dysfunction in diabetic rats (22,23). Several studies demonstrate that H 2 S is an antioxidant that regenerates GSH and lowers oxidative stress (5)(6)(7)11). Our recent study reported that supplementation with H 2 S increases glucose utilization and decreases secretion of the proinflammatory biomarkers IL-8 and MCP-1 in adipocyte and monocyte cell models (11,19).…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous H 2 S supplementation reduces blood pressure, decreases atherosclerotic plaque size compared with those of controls in apolipoprotein E knock-out mice, and prevents progression of diabetic nephropathy in spontaneously hypertensive rats and endothelial dysfunction in diabetic rats (22,23). Several studies demonstrate that H 2 S is an antioxidant that regenerates GSH and lowers oxidative stress (5)(6)(7)11). Our recent study reported that supplementation with H 2 S increases glucose utilization and decreases secretion of the proinflammatory biomarkers IL-8 and MCP-1 in adipocyte and monocyte cell models (11,19).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is logical to speculate that inhibiting Hcy-induced ER stress may be a novel therapeutic strategy to prevent and ameliorate AD progression. Hydrogen sulfide (H 2 S), the third gaseous mediator, has recently been recognized as an important endogenous neuromodulator and neuroprotectant [26][27][28][29] . The most recent in vitro studies by our group have demonstrated that Hcy-associated neurotoxicity to PC12 cells is due to reduced endogenous generation of H 2 S [30] and that supplementation of sodium hydrosulfide (NaHS), the H 2 S-donor, ameliorates the Hcy elicited-neurotoxicity in PC12 cells [31] .…”
Section: Introductionmentioning
confidence: 99%
“…Physiologically, H 2 S is produced by three enzymes, namely cystathionine-␤-synthase (CBS), cystathionine-␥-lyase (CSE), and 3-mercaptopyruvate sulfurtransferase (3MST) (18). With few exceptions, the enzymatic pathways for H 2 S production are tissue specific.…”
mentioning
confidence: 99%
“…For example, CBS is the main H 2 S-generating enzyme in the nervous system (16), CSE in the vascular system (43). On the other hand, 3MST is primarily located in the mitochondria (18). Interestingly, all the three enzymes are present in the kidney (17).…”
mentioning
confidence: 99%